Imagining Hope William F. Lynch's Psychology of Hope - Capps, Donald 1939- (2016)
This article is a follow-up to my recent article on Erving Goffman's Asylums (), an analysis of the mental hospital environment. I focus here on William F. Lynch's book Images of Hope () which was written when Lynch was a scholar in residence at St. Elizabeths Hospital in Washington, D.C. in . I take particular note of the fact that Lynch perceived the book to be a venture into the psychology of hope, and that he based this psychology on the complementary relationship of hope and imagination. I also consider the relationship that he draws between hope and help; the dynamic of hope and hopelessness; the roles of wishing and waiting in the development of a mature sense of hope; and the imagination as an instrument of coping. I conclude that among the selves that comprise our composite Self, the hopeful self is essential to life itself.
Keywords: Adjustment (Psychology); Despair; Erving Goffman; Help; Hope; Hope; Hopelessness; Imagination; Imagination; Leslie H. Farber; LYNCH, William F; Psychiatric hospitals; Psychological aspects; Self-fragmentation; The hopeful self; Waiting; William F. Lynch; Wishing